MODEL LOGIKA FUZZY SUGENO BERBASIS WEB UNTUK SELEKSI PENERIMA BEASISWA - Heru Supriyono, Achmad Kurnianto, Muhammad Fikri Khaidir, Sujalwo (STMIK Sinar Nusantara, 2018)
One of the main problems emerging in the decision making process by human is the possibilities of bias decision caused by personal factors. This paper discusses the development of a Fuzzy Sugeno based decision support systems for selecting scholarship recipients which is implemented in a web based systems. The main objectives of the research are to result a Fuzzy Sugeno model which mimic human reasoning in the scholarship selection and to calculate recommendation value of every applicant. There are five factors used in the computation involving grade point average (GPA), parent’s income, number of sibling, organization activities, and achievement. Traditional system development life cycle or waterfall method was used in the system development process. Fuzzy Sugeno model is implemented mainly using Django framework with Python programming language. The result of the research is the web based decision support systems for selecting scholarship recipient. The blackbox testing of the decision support systems showed that all functions of the systems are functioning well as expected and the validation testing result using real data showed that the validity level I equals to 92.3 %.